Identifying correlations between donor demographics and isohemagglutinin titers as a potential method to screen for low-titer group O whole blood. (February 2021) - Jacob, Reuben P.; Wang, Duan; Hodghead, Kathryn; Pham, Tho D.
Abstract: Background: With more hospitals using low-titer group O whole blood in trauma resuscitation, having an efficient screening method for low-titer donors is critical. Our blood center uses an automated screen for high-titer isohemagglutinins in our platelet donations while collecting detailed donor demographic information. Using this data, we can identify key demographics often associated with titer status, thereby helping develop a donor-triaging method for titering. Study Design and Methods: Titer results were read with an automated microplate system as either high or low, based on agglutination, with a cutoff equivalent to 1:256 (both anti-A and anti-B). Donor demographic data analyzed included date of donation, blood group, age, gender, and ethnicity. Results: 57, 508 donations were collected from 2073 unique donors between 2014 and 2018. We found the following demographics to be correlated with titer status: gender, ABO blood group, age, and ethnicity. Variability in titer status was identified in 215 individuals. This represented around 10 % of the total unique donors and was split equally amongst gender. We also found that donors between the ages of 41–60 ha d the highest likelihood of having variability in titer status, peaking at 13 %, and this proportion declined past age 60. Conclusion: Titer status is associated with the following donor demographics: gender, ABO type, age, and ethnicity. We also discovered that variability in titer status is correlated with age. In blood centers that do not have automated and routine titer screening procedure, these findings could be used as a method to efficiently identify low-titer donors a-priori.